Specific features of praseodymium extraction by intergel system based on polyacrylic acid and poly-4-vinylpyridine hydrogels - Jumadilov, T.K.; Malimbayeva, Z.B.; Khimersen, Kh.; Saparbekova, I.S.; Imangazy, A.M.; Suberlyak, O.V. (KU Publ., 2021)
Some technological solutions contain valuable components and can become an additional source of rare-earth elements to satisfy the current production demands. This research provides the study on using a combination of polyacrylic acid hydrogel (hPAA) and hydrogel of poly-4-vinylpyridine (hP4VP) in different molar ratios for praseodymium ions sorption from its nitrate solution. The mutual activation of the hydrogels in an aqueous medium provides their transformation into a highly ionized state by the conformational and electrochemical changes in properties during their remote interaction. The electrochemical properties of solutions were studied by the methods of electrical conductivity, and pH measurements of the solutions. The research showed that the maximum activation of hydrogels was revealed within the molar ratio of hPAA:hP4VP equal to 1:5. Moreover, the total praseodymium ions sorption degree after 24 hours of sorption by individual hPAA and hP4VP was 54 % and 47 %, respectively, whereas the praseodymium ions sorption degree by the hPAA–hP4VP intergel system in the molar ratio 1:5 became 62 %. A slight increase in the sorption degree of praseodymium ions by the intergel system in comparison with individual hydrogels can be explained by the achievement of a higher ionization degree of hydrogels being activated in the hPAA–hP4VP interpolymer system by the remote interaction effect.
Полиакрил қышқыл мен поли-4-винилпиридин интергельдік жүйесімен празеодимді бөлудің ерекшеліктері
Особенности извлечения празеодима интергелевой системой на основе гидрогелей полиакриловой кислоты и поли-4-винилпиридина
Keywords: intergel systems; polyacrylic acid hydrogel; poly-4-vinylpyridinehydrogel; remote interaction; sorption; praseodymium ions